PHYSICAL AND PHYSICOCHEMICAL CHARACTERIZATION OF SAPODILLA(MANILKARA ZAPOTA (L.) P. ROYEN) FROM BELÉM, PARÁ (REMUNOM, 2026)
Sapodilla is an Amazonian fruit with relevant nutritional and functional potential yet remainsunderexplored. This study aimed to characterize the physical and physicochemical properties offruits and pulps marketed in Belém do Pará and compare two harvests using statistical analyses. pH,electrical conductivity, moisture, density, soluble solids, and acidity were determined following officialmethods. The results showed that sapodilla fruits are rounded and have a good pulp yield, withphysicochemical properties similar to those found in the literature, and presented values for somevariables that were not found in the literature. Furthermore, only the acidity of the pulp showed asignificant variation between the two harvests. These findings highlight the importance ofphysicochemical profiling for quality control and industrial standardization.